Biodegradation of n-alkanes in crude oil by three identified bacterial strains. (1st September 2020) - Liu, Yuan; Wan, Yun Yang; Wang, Chunjiang; Ma, Zheyu; Liu, Xiaoli; Li, Shengjin
Graphical abstract: Highlights: Lab simulation of selected biosurfactant-producing bacteria, good candidates for bioremediation. Report semiquantitative data for C14 –C35 n -alkanes during biodegradation. Reveal the very different biodegradation behaviors of the three bacteria. Found that the biodegradation rates of n -alkanes follow first-order kinetics under the experimental conditions. Clarify that bacteria simultaneously biodegrade C14–C35 n -alkanes at various ratios and rates. Abstract: In this study, aerobic biodegradation of crude oil was simulated using Pseudomonas aeruginosa XJ16, Bacillus cereus XJ20, and Acinetobacter lwoffii XJ19 bacteria for 90 days, for semi-quantitative calculation of concentration, demonstrating that n -alkanes (C14 –C35 ) were biodegraded by the three strains at different ratios and rates. P . aeruginosa XJ16 showed the highest biodegradative potential for n -alkanes, with total biodegradation ratio of 98.2% in 10 days. In comparison, the total biodegradation ratio by B . cereus XJ20 increased gradually and achieved 98.8% after 90 days; whereas that by A . lwoffii XJ19 was much lower even after 90 days (29.3%). In addition, P . aeruginosa XJ16 and B . cereus XJ20 exhibited stronger biodegradation efficiencies for C18 –C32 n -alkanes (95.4%–99.7%) than A. lwoffii XJ19 (9.05%–73.0%). However, all three bacterial strains exhibited comparably good biodegradation efficiencies for C33 –C35 n -alkanes (60.2%–86.4%). Moreover, the biodegradation rate constants and biodegradation rates were of the decreasing order: P . aeruginosa XJ16 >  B . cereus XJ20 >  A . lwoffii XJ19. P . aeruginosa XJ16 and B . cereus XJ20 biodegrade n -alkanes with relatively low carbon numbers more easily than those with high carbon numbers. However, A . lwoffii XJ19 is more likely to biodegrade n -alkanes with relatively high carbon numbers. On day 10, surface tension (mN·m −1 ) declined from 70.6 to 35.9 by treatment with P . aeruginosa XJ16, to 31.3 with B . cereus XJ20, and to 34.1 with A . lwoffii XJ19. As biosurfactant-producing and hydrocarbon-degrading bacteria, these three strains have the potential to be used for bioremediation of hydrocarbon pollutants.